Modifying flow in the ACA–ACoA complex: endovascular treatment option for wide-neck internal carotid artery bifurcation aneurysms. (10th April 2014) - Nossek, Erez; Chalif, David J; Levine, Mitchell; Setton, Avi
Abstract : Background: Treatment of selected wide-neck internal carotid artery (ICA) bifurcation aneurysms remains challenging for clip reconstruction and for endovascular options. Objective: To describe a new endovascular treatment technique for wide-neck ICA bifurcation (ICAb) aneurysms. Methods: We have employed a treatment approach that uses both complete proximal occlusion and reversal of flow in the ipsilateral A1 segment, using different endovascular modalities such as coils, stent-assisted coiling, or flow diverters (FDs) plus coiling concomitantly. This endovascular technique may overcome the challenges of current treatments and high recanalization rates for coiled ICAb aneurysms. Results: We treated four patients in whom we redirected the pre-existing flow in the supraclinoid ICA into the ipsilateral A1 and M1 segments, to a new unilateral, linear flow from the supraclinoid ICA solely into the ipsilateral M1 segment. This resulted in the establishment of flow from the contralateral A1 segment into the ipsilateral A1 segment, allowing supply of only demanding perforating arteries on this specific (ipsilateral) segment. This technique was not associated with any new neurological deficits or radiographic ischemia. The four patients reviewed were all treated using coils. One was treated with a standard stent. The other two were treated with a FD. Conclusions: We found that the proposed technique of flow modification can allow for hemodynamic conversion of ICAb to 'side-wall' aneurysm. In patients with good collateral flow through the anterior communicating complex, this treatment paradigm is safe and effective.